2016
DOI: 10.1120/jacmp.v17i6.6347
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dosimetric differences between the TMR 10 and convolution algorithm for Gamma Knife stereotactic radiosurgery

Abstract: Since its inception, doses applied using Gamma Knife Radiosurgery (GKR) have been calculated using a simple TMR algorithm, which assumes the patient's head is of even density, the same as water. This results in a significant approximation of the dose delivered by the Gamma Knife. We investigated how GKR dose calculations varied when using a new convolution algorithm clinically available for GKR planning that takes into account density variations in the head compared with the established calculation algorithm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…Several reports have appeared in the literature comparing the two algorithms. [65][66][67][68][69][70][71][72][73] These reports indicate that using the convolution algorithm as opposed to TMR10 for the same treatment plan (i.e., for the same shot arrangement and prescription dose) tends to increase the total treatment time by between about 4% and 10%, depending on the tumor type and location, without significant change in the dose distribution. 73 Thus, slightly higher doses are effectively delivered using the convolution algorithm instead of the standard dose algorithm.…”
Section: B3 Treatment Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have appeared in the literature comparing the two algorithms. [65][66][67][68][69][70][71][72][73] These reports indicate that using the convolution algorithm as opposed to TMR10 for the same treatment plan (i.e., for the same shot arrangement and prescription dose) tends to increase the total treatment time by between about 4% and 10%, depending on the tumor type and location, without significant change in the dose distribution. 73 Thus, slightly higher doses are effectively delivered using the convolution algorithm instead of the standard dose algorithm.…”
Section: B3 Treatment Planningmentioning
confidence: 99%
“…Although the convolution method is inherently more accurate than simpler ray‐tracing dose calculations, as of this writing, it has not been widely adopted in GSR. Several reports have appeared in the literature comparing the two algorithms 65–73 . These reports indicate that using the convolution algorithm as opposed to TMR10 for the same treatment plan (i.e., for the same shot arrangement and prescription dose) tends to increase the total treatment time by between about 4% and 10%, depending on the tumor type and location, without significant change in the dose distribution 73 .…”
Section: Treatment Process Quality Assurancementioning
confidence: 99%
“…The dose differences between the TMR 10 and convolution algorithms correlate well with other reported studies. Rojas‐Villabona et al reported that dose calculations generated by the convolution algorithm closely matched the measurement values with an average treatment time that was 5.9% longer than in the TMR 10 algorithm 24 . Choi et al reported that Monte Carlo dose calculations were lower than those calculated by TMR 10 by about 4% 25 …”
Section: Discussionmentioning
confidence: 85%
“…These algorithms have been compared in previous studies. [4][5][6][7][8] It was found that the convolution algorithm provided greater accuracy to films within a RANDO phantom to dose distributions than that with TMR10. 4 This conclusion was supported by Nakazawa et al, 5 who advocated the use of convolution algorithm to reduce dosimetric uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed the convolution algorithm reducing dose to cochlea by 7% when compared to TMR10. 7 Treatment times were studied in one paper revealing an 8•4% larger average treatment times for identical prescriptions and shot arrangements when the convolution dose calculation was used compared to the TMR10 algorithm. 8 When implementing new dose calculation algorithms, special considerations must be given to the dose prescription.…”
Section: Introductionmentioning
confidence: 99%